Evaluate the expression for f = –9. Simplify your answer.

f/ f + 10
=

1 answer

To evaluate the expression \( \frac{f}{f + 10} \) for \( f = -9 \), we start by substituting \(-9\) for \(f\):

\[ \frac{f}{f + 10} = \frac{-9}{-9 + 10} \]

Next, we simplify the denominator:

\[ -9 + 10 = 1 \]

Now we can substitute this result back into the expression:

\[ \frac{-9}{1} = -9 \]

Therefore, the simplified answer is:

\[ \boxed{-9} \]

Similar Questions
  1. how does a rodeo star get around??well if you cant give me an answer can you help me. heres the instructions First Simplify the
    1. answers icon 5 answers
  2. ***show workevaluate the expression: 7^-6 (-6)^-9 simplify the expression. write your answer using only positive exponents.
    1. answers icon 2 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions